Ankle fusion in patients with haemophilia. (13th March 2013) - Bluth, B. E.; Fong, Y. J.; Houman, J. J.; Silva, M; Luck, J. V.
Summary Ankle fusion in patients with haemophilia is a well‐accepted treatment for end‐stage arthropathy. However, current published outcome data are based on small sample sizes and generally short‐term follow‐up. The aim of this study was to evaluate the long‐term results of ankle fusion in a large group of haemophilic patients treated at a single institution. The results of 57 ankle fusions performed on 45 patients between 1971 and 2010 were reviewed retrospectively. Data were gathered for type and severity of haemophilia, HIV status, fixation technique, postoperative complications and requirement of additional surgeries. A modified American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score was calculated for 20 ankles available for follow‐up. Patients were followed for a mean of 6.6 years. There were no intra‐operative or immediate postoperative complications related to fusion of the ankle. The overall non‐union rate was 10.4% for tibio‐talar fusion and 8.3% for sub‐talar fusion. This rate was reduced to 3.7% and 5.6%, respectively, after the introduction of newer surgical techniques in 1995. None of these non‐unions required revision surgery. The modified AOFAS scale demonstrated that 75% had no pain in the operated ankle a mean of 7.2 years following surgery. The remaining 25% scored their average pain as 3 of 10. The functional portion of the score suggested that patients have good alignment, minimal activity limitations or gait abnormalities, and can walk long distances. We conclude that ankle fusion successfully relieves pain and provides a good functional outcome. It is an appropriate treatment for end‐stage haemophilic arthropathy of the ankle.